Desenvolvimento inicial de um plantio misto de Eucalyptus urograndis e Acacia mearnsii em sistema agrossilvicultural - Viera, Márcio (2010)
Understanding the initial development in consortiated systems are vital to decide about practices to obtain a sustainable productivity, in relation to environmental resources in an agrossilvicultural site. Due to this, this study had as objective: - to evaluate the agricultural productivity in agroforestry systems with different arrangements of the forest species; - to determine the biomass and nutrients accumulation in different species involved in the system; - to evaluate initial growth of monospecifical and mixed stands of Eucalyptus urograndis and Acacia mearnsii; - to determine soil occupation by root system of Eucalyptus urograndis and Acacia mearnsii in monoespecifical and mixed stands and also Acacia mearnsii nodules in these systems. For that, an experimental field was installed in Bagé-RS, which is composed by five treatments with simple combination and arrangements of Eucalyptus urograndis (E) and Acacia mearnsii (A) (100E; 100A; 50E:50A; 75E:25A e 25E:75A), in a randomized blocks design, with three repetitions, with corn cultivaded in the six first months. Growth evaluations for the aerial part in agroforestry system were done at 6 and 18 months age, and root system evaluation was done at of 8 and 18 months age. Initial growth in diameter, total height and wood production of Eucalyptus urograndis and Acacia mearnsii didn t differ significantly (p < 0.05) in different treatments. Forest species consortion provided a positive interspecific effect in Eucalytpus urograndis leaf area index. Total above ground biomass was statistically equal (p < 0.05) between monocultive and mixed stands of forest species, but when it was evaluated in compartments, a competitive interspecific interaction was observed of eucalyptus upon black-wattle, causing a reduction on crown biomass formation. Total production of maize (Zea mays), consortiated with monoespecifical and mixed stands of forest species, did not differ statistically (p > 0.05) among the tested treatments. Due to the great nutrients export through maize harvest, it is necessary, even with straw maintenance in agroforestry systems, to make a nutritional reposition, mainly with P and N in the following cultives, because of the great amount that are exported through grains, which comes to 68,1 and 51,7%, respectively, in relation with the total accumulated on biomass. Root system, independent of cropping system, reaches a maximum projection in the vicinity of 120 cm from the stem of the tree at 8 months old, although at 18 months it reaches the whole utile are in each tree. Fine roots density at 8 months, both for root system length and biomass for Eucalyptus urograndis and Acacia mearnsii in monoculture and in mixed stands, show the same behavior for soil layers occupation. Interespecif interactions and intraespecific interactions were not observed between root systems of eucalyptus and blackwattle, until 18 months. Nodules biomass showed a very variable distribution and didn t show differences between monocultive and mixed stand of Acacia mearnsii. Higher density of roots and nodules is located in the layer from 5 10 cm depth, close to tree stem followed by diagonal and planting inter-row. Nutrients competition can be considered as minimum, between mayze and forest species, due to its small root system projection during crop cultivation (6 initial months).